Hubungan pola aktivitas dan kecemasan dengan kejadian leukorea pada remaja - Andri Nur Sholihah (Universitas Muhammadiyah Semarang, 2020)
Biological changes in adolescents exert a very dominant influence on hormonal mechanisms. One of them is the occurrence of leukorrhea as a result of biological changes in adolescents. But this leukore also can not be ignored, because leukore can be a sign of certain diseases. The purpose of this study was to identify the incidence of leukorrhea in adolescents, anxiety in adolescents, and patterns of adolescent activity, and the relationship between patterns of activity and anxiety with leukorrhea in adolescents. Research design using observational analytic research with cross sectional approach. The population was students of Aisyiyah University in Yogyakarta. Samples of 71 girls were taken by random sampling technique. Data collection techniques used to collect primary data using a structured questionnaire. The data obtained were then analyzed using the univariate formula (frequency distribution formula) and bivariate (Chi square formula). The results of Leukore occurrences in adolescent girls by 79% and those without vaginal discharge by 21%. 49 adolescents experienced a 67% abnormal activity pattern and the remaining 24 adolescents experienced a 33% normal activity pattern. 26% of students experienced anxiety and moderate anxiety 36%, mild anxiety 11% and those without anxiety as much as 17%. The results of the analysis stated that the most respondents with abnormal activity patterns and experienced vaginal discharge as much as 48%. From the results of the analysis with the chi-square test, the level of closeness of the relationship between the two variables showed a significant value of 0.014 (p <0.05). There is a correlation between activity patterns with the incidence of vaginal discharge in adolescents and most respondents with severe anxiety and experiencing vaginal discharge as much as 34%. From the results of the analysis with the chi-square test, the level of closeness of the relationship between the two variables showed a significant value of 0.01 (p <0.05). There is a relationship between anxiety level and the incidence of vaginal discharge in young women.